Tata Ruang Wilayah Peternakan Kambing di Kabupaten Lampung Utara dalam Mendukung Kedaulatan Pangan: Regional Spatial Planning for Goat Farming in North Lampung Regency to Support Food Sovereignty - Putra, Boby Arya; Gunanto, Sigit; Fauzi, M.; Hartadi, Subagus (Journal of Integrated Agribusiness, 2024)
Goats are a prominent commodity within the ruminant livestock sector, serving as the primary meat producer to meet national demands. To support the development and productivity of goat farming, it is crucial to establish suitable spatial and regional planning frameworks for breeders. North Lampung is one of the regencies in Lampung Province with significant potential for goat farming, supported by a diverse vegetation profile and abundant agricultural waste for feed. Agricultural production in North Lampung reaches 61,823 tons annually, with rice as the primary crop, while livestock production totals 1,847,319 tons per year. The region provides 64,915 hectares for food crops and 128,563 hectares for plantations, with a goat population of 82,849. This potential enables North Lampung Regency to become a prominent goat farming area. However, the regency lacks standardized spatial planning and mapping for goat farming areas. This study identifies and analyzes the potential for goat farming development in North Lampung Regency using two stages: (1) identifying and analyzing goat farming potential through Location Quotient (LQ) analysis to determine farming centers, and (2) creating a goat farming development map for North Lampung Regency using Corel Draw/GIS. The map will outline regions suitable for goat farming as a foundation for government policy in North Lampung. The results identify 11 sub-districts, out of the 23, that can serve as business centers for goat farming development in North Lampung Regency. This research serves as a reference for the Lampung Provincial Government and related stakeholders in future goat farming policy decisions in North Lampung Regency.